Prevalence of arterial hypertension and lifestyles in people over 35 years of age in the town of Huánuco - 2011 - Ríos Rojas, Maura (2017)
The objective of the investigation was to determine the influence of the socioeconomic factors in the academic performance of the pupils of the first year of the Nursery School - I academic semester UNHEVAL - Huánuco - 2010, with a sample population of 80, the study was a descriptive, the socioeconomic survey being applied and for the academic performance, information of the unit of academic records that were processed across the statistical program SPSS version 7.0, using the statistical test of square Chi; with the following results: 63.8 % lives with his parents, the level of education of the father of the majority was secondary and top and of the secondary mother; 72.5 % resides in urban zones with possession of own housing 67.5 %; 98 % with basic services of water, outlet and light, unlike 13 % with Internet services, the economic support there is facilitated by the parents by monthly income salary minor of S/. 500, 40 % and 32.5 % from 500 to 1000 nuevos soles, the majority of they are independent and some workers in public entities, Likewise it estimated the academic performance, considering that 100 % was registered by 22 credits and 07 subjects, of which 38.8 % approved all the subjects and credits, but by an academic regular performance (57.5 %) by averages weighted from 11 to 13 respectively. In conclusion the results obtained in the investigation us demonstrate that the socioeconomic factors of the students were of average level what determined the academic regular performance.